Association between local indoor smoking ordinances in Massachusetts and cigarette smoking during pregnancy: a multilevel analysis. Issue 1 (13th December 2011) - Nguyen, K H; Wright, R J; Sorensen, G; Subramanian, S V
Abstract : Objective: To estimate the association between local clean indoor air ordinances and prenatal maternal smoking across 351 municipalities in Massachusetts before the 2004 statewide ban and to test the effect of time since ordinance adoption on the association. Methods: The authors linked 2002 birth certificate data of women who gave birth in the state and reported a Massachusetts residence (n=67 584) to a database of indoor smoking ordinances in all municipalities. Multilevel regression models accounting for individual- and municipality-level variables estimate the associations between the presence of local smoking ordinances, strength of the ordinances, time since ordinance adoption and prenatal smoking. Results: Compared with those living in municipalities with no ordinances, women living in municipalities with a smoking ordinance had lower odds of prenatal smoking (OR=0.72, CI=0.53 to 0.98). No effect was found for 100% smoke-free ordinances. For the analyses testing the effect of time, pregnant women living in municipalities with ordinances enacted >2 years were less likely to smoke than those in municipalities with more recent (<1 year) ordinances. Conclusions: Preventing smoking among women of reproductive age is a public health priority. This study suggests that indoor smoking ordinances were associated with lower prenatal smoking prevalence and the favourable effect increased over time. Findings highlight the public health benefit of tobacco control policies.